Hasil Pengembangan Booklet Tumbuhan Berpotensi Anti Fertilitas Di Kecamatan Lebong Selatan Kabupaten Lebong: (Results of the development of a plant booklet with the potential for anti-fertility in South Lebong District, Lebong Regency) - Erika Neti; Nopa Nopiyanti Nopa Nopiyanti; Sepriyaningsih Sepriyaningsih (BIODIK, 2023)
This study aims to determine the results of the development of an booklet for potentially anti-fertility plants in South Lebong District which is used as a medium of information about anti-fertility plants. This research is a quantitative descriptive research. Samples were taken by exploratory or roaming methods and booklet development was made using the Borg and Gall development model. Booklet development was carried out through five stages of research and development, namely 1) Research and data collection stage 2) Planning stage, 3) Product draft development stage, 4) Initial field test stage, and 5) Revision stage of the trial results and final product. The results of the development of an exploration booklet for potentially anti-fertility plants in Lebong Selatan District were validated by 3 expert lecturers from PGRI Silampari Lubuklinggau University, namely the material expert validator with a score obtained of 85%, a media expert with a value obtained of 83%, a linguist with a value obtained of 81 %, and continued with the community readability test through trials on a small group of 12 people with a score of 90%. It can be concluded that the booklet that has been developed is valid and does not need revision and is very suitable to be used as a source of information about potentially anti-fertility plants. Key words: Booklet, Plants, Anti fertility Â  ABSTRAK Penelitian ini bertujuan untuk mengetahui hasil pengembangan booklet tumbuhan berpotensi anti fertilitas di Kecamatan Lebong Selatan yang digunakan sebagai media informasi mengenai tumbuhan anti fertilitas. Penelitian ini adalah penelitian deskriptif kuantitatif. Sampel yang diambil dengan metode eksploratif atau jelajah dan pengembangan booklet dibuat dengan menggunakan model pengembangan Borg dan Gall. Pengembangan booklet dilakukan melalui lima tahap penelitian dan pengembangan yaitu 1) Tahap penelitian dan pengumpulan data 2) Tahap perencanaan, 3) Tahap pengembangan drafÂ  produk, 4) Tahap uji lapangan awal, dan 5) Tahap revisi hasil uji coba dan produk akhir. Hasil pengembangan booklet eksplorasi tumbuhan berpotensi anti fertilitas di Kecamatan Lebong Selatan di validasi oleh 3 dosen ahli dari Universitas PGRI Silampari Lubuklinggau yaitu validator ahli materi dengan nilai yang diperoleh 85%, ahli media dengan nilai yang diperoleh 83%, ahli bahasa dengan nilai yang diperoleh 81%, dan dilanjutkan uji keterbacaan masyarakat melalui uji coba kepada kelompok kecil sebanyak 12 orang dengan nilai yang diperoleh 90%. Dapat disimpulkan booklet yang telah dikembangkan valid dan tidak perlu revisi serta sangat layak digunakan sebagai sumber informasi mengenai tumbuhan berpotensi anti fertilitas. Kata kunci: Booklet, Tumbuhan, Anti fertilitas